Immunogenicity and safety of two-dose SARS-CoV-2 vaccination via different platforms in kidney transplantation recipients - Chen, Chien-Chia; Huang, Yi-Jen; Lai, Mei-Jun; Lin, Min-Huey; Lin, Wei-Chou; Lin, Hui-Ying; Lin, Yu-Chun; Huang, Yu-Tsung; Lee, Ya-Fen; Tsai, Meng-Kun; Lee, Chih-Yuan (Frontiers in Immunology, 2022)
After kidney transplantation, patients had a poor response to vaccination for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The efficacy and adverse effects of vaccines from different platforms in these patients remain unclear. We prospectively analyzed both anti-spike protein antibody and cellular responses one month after the first and second doses of SARS-CoV-2 vaccines in 171 kidney transplant patients. Four vaccines, including one viral vector (ChAdOx1 nCov-19, n = 30), two mRNA (mRNA1273, n = 81 and BNT162b2, n = 38), and one protein subunit (MVC-COV1901, n = 22) were administered respectively. Among the four vaccines, mRNA1273 elicited the strongest humoral response, as well as the highest interferon-γ levels in patients with positive cellular response against spike protein. Antiproliferative agents were negatively associated with both the antibody and cellular responses. Transient elevation of creatinine levels was noted in about half of the patients after the first dose of mRNA1273 or ChadOx1, and only one of them presented borderline cellular rejection without definite causality to vaccination. In conclusion, the mRNA vaccines had better immunogenicity than the other platforms. Renal function needs to be carefully monitored after vaccination. Vaccination strategies should be tailored according to transplant status and vaccine characteristics.